Are real estate and securities markets integrated / Nurliza Abd Aziz - Abd Aziz, Nurliza (2007)
Using the property and equity markets operating in Malaysia, this study examines the question of whether the real estate market and securities market are integrated over a period 1997-2006. In this case, there are only two asset classes that will be used as the variables that are, the general market for financial assets which represent the securities market, and the general market for physical real estate assets which represent the real estate market. Multiple Regression Analysis will be used to examine the relationship between the real estate market and the securities market. The real estate market is represented by the house and apartment index while the securities market is represented by the KLCI and property index. This study will use data from general stock market index (KLCI), property index, house index and apartment index. The overall results show that changes in securities market lead to changes in real estate market. Besides, the results also indicate that there is a positive relationship between KLCI and real estate assets which are house and apartment. However, for property index, the results indicate negative relationship with house and apartment.